Acute Myelogenous Leukemia With Trisomy 8 and Concomitant Acquired Factor VII Deficiency. (September 2019) - Moosavi, Leila; Bowen, Jonathan; Coleman, Jeffrey; Heidari, Arash; Cobos, Everardo
Acquired isolated factor VII deficiency is a rare bleeding disorder and has been reported in 31 cases. This is in contrast to congenital factor VII deficiency, which while also infrequent is the most common rare congenital bleeding disorder. Acquired isolated factor VII deficiency has been described primarily in patients with solid malignancies, sepsis, and in the presence of anti-factor VII autoantibodies. We report a case of acute myelogenous leukemia with an associated trisomy 8 cytogenetic abnormality presenting with factor VII deficiency. The factor VII deficiency cleared after induction chemotherapy and with the disappearance of the cytogenetic and molecular abnormalities. We discuss a possible link between trisomy 8 and vitamin K metabolism, which might result in acquired factor VII deficiency in acute myelogenous leukemia.